Placental malaria in Owerri, Imo State, South-Eastern Nigeria - Ukaga, C N; Nwoke, B E; Udujih, O S; Ohaeri, A A; Anosike, J C; Udujih, B U; Nwachukwu, M I (Tanzania Journal of Health Research, 2008)
No Abstract. Tanzania Health Research Bulletin Vol. 9 (3) 2007: pp. 180-185